The Role of Notarial Deed in Protecting Trademark License Holders - Marulitua, Gihon (CV. Publikasi Indonesia, 2025)
Trademark License; Notarial Deed; Legal Protection; Intellectual Property.This study examines the role of notarial deeds in providing legal protection for parties involved in trademark licensing agreements in Indonesia. A trademark license agreement allows the registered trademark owner to grant permission to another party to use their mark. Although not legally required to be made in the form of a notarial deed, in practice, such deeds significantly enhance legal certainty and evidentiary strength, especially when the agreement is registered with the Directorate General of Intellectual Property (DGIP). Through normative legal analysis and interviews with practitioners and academics, this research finds that notarial deeds add substantial value in ensuring legal protection and facilitating dispute resolution. Moreover, the authority of notaries as public officials guarantees neutrality and the legitimacy of the licensing process. The study recommends harmonizing existing legal norms with practical application and encourages improved understanding of intellectual property law among notaries. Therefore, a notarial deed should not be viewed merely as a formal requirement, but as a vital legal instrument in securing rights and obligations in trademark licensing relationships.